Efficacy of a spot-on combination product containing selamectin and sarolaner (Stronghold® Plus) in the treatment of naturally occurring Notoedres cati infestations in cats - Borowski, Stasia; Berlamont, Helena; Geurden, Thomas; D’Hanis, Lina; Rapti, Dhimiter; Cvejić, Dejan; Suckstorff, Oliver; Simović, Nikola; King, Vickie L. (Frontiers in Veterinary Science, 2025)
Notoedric mange (also known as feline scabies) is a highly contagious and intensely pruritic dermatologic condition of cats caused by infestation with Notoedres cati mites. Previous publications provide evidence that topical selamectin, and more recently, topical selamectin + sarolaner is efficacious in the treatment of notoedric mange in cats. The study reported here was conducted to confirm the efficacy of a topically applied combination of selamectin and sarolaner (Stronghold® Plus) in the treatment of notoedric mange in cats naturally infested with N. cati. Client-owned cats with clinical signs of notoedric mange and positive for live N. cati mites were enrolled and allocated randomly to treatment with either placebo (n = 10) or Stronghold Plus (n = 10). Treatment was administered on Days 0 and 30, and skin scrapings to detect live mites and assessment of the clinical signs of notoedric mange were conducted on Days 0, 30, and 60. The primary efficacy evaluation was based on the percent reduction in live mite counts in Stronghold Plus-treated cats compared to placebo-treated cats on Day 30. The parasitological cure (i.e., no live mites found) on Days 30 and 60 was also calculated for both treatment groups, as well as the improvement in clinical signs of notoedric mange. A single topical administration of Stronghold Plus provided a significant (p < 0.0001) and 100% reduction in live N. cati mites relative to placebo within 30 days. All placebo-treated cats harbored mites on Days 30 and 60, while none of the Stronghold Plus-treated cats had any live mites. Parasitological cure on Days 30 and 60 was thus 100% and significantly different than placebo (p < 0.0001). Clinical signs of notoedric mange improved in the Stronghold Plus-treated cats by Day 30, and no signs of notoedric mange were observed by Day 60. This study confirms that Stronghold Plus is highly effective in the treatment of notoedric mange in cats naturally infested with N. cati.